(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
COVID-19 is intensely disturbing life and living patterns through out the universe. Confinement, limitations of contact and closure of financial force leading to a total change to working culture and psycho-social environment which impacted people in the world. Such unusual boundations significantly threaten the mental health of people that includes all working and nonworking people. Regardless of the way that COVID-19 situation also provides openings for individualal growth and strengthen connection among family members, counterbalance the shortcomings. Uneasiness, absence of friends’ contact and decreased privileges mental strain guidelines of different people in different countries are the point of anxiety. Eexpanded danger for individuals’ psychological instability and aggressive behavior is another main threat at home and at working spot. To keep up with ordinary and crisis individuals’ psychological attention is a big fundamental to confine lengthy stretch implications for the working individuals. Critical assessment questions include understanding the enthusiastic prosperity effects of social isolating and financial squeezing factor, perceiving danger and strength factors, and hindering long stretch results.